Principles and methods for the assessment of nephrotoxicity associated with exposure to chemicalsNephrotoxicity associated with exposure to chemicals, principles and methods for the assessment of (Environmental health criteria)
El texto completo se encuentra disponible en la página: http://www.inchem.org/pages/ehc.html